Profile of patients with Multiple sclerosis in Mosul City - Mohammed Saleh Mohammed; Ali Neamat Sulaiman Alallaf (College of Nursing,University of Mosul, 2020)
Background: This study was carried out to assess the prevalence of MS in Mosul City. Methods: A retrospective study was applied in Mosul City for the period between (2020-2000). MS patient's outpatient of Ibn-Sina Teaching hospital in Mosul City. Assessment of MS status: for the assessment of MS status the Kurtzke EDSS was used. EDSS was based on ten scores (0-10) and categorized the MS severity into three level; mild disability (EDSS, 0.0 to 3.5), moderate disability (EDSS, 4.0 to 6.5), and severe disability (EDSS, 7.0 to 9.5). Microsoft Excel file was used to analyzed the data, number, percentage, Mean and Standard deviation were computed analyze all demographic and clinical variables. This study was approved by the Ethics Committee of the Mosul Health Directorate, at Mosul City -Iraq. Results: the study found that the mean age of patients (34.7) among men and (32.9) among women. The mean age at onset is (28.9) among men and 27.9 among women. In relation to family history 89.8% of men and 93.9% of women don't have positive family history with MS. The majority of patent have Relapsing- remitting. Conclusion: In conclusion, the prevalence of MS has been steadily rising in the Mosul city over the past few decades. Key words: profile, Multiple Sclerosis, Mosul